Floral aroma improvement via solar withering and shaking in summer green tea: Sensory and analytical insights - Jiarui Zeng; Sijia Lv; Rou Zeng; Jiayuan Lin; Jie Jiang; Qiang Shen; Yuanchun Ma; Wanping Fang; Jingjing Tian; Xujun Zhu (Food Chemistry: X, 2025)
Summer green tea leaves often exhibit excessive astringency, weak aroma and poor sensory quality, leading to low consumer acceptance, resource waste, and economic losses, which contradict sustainable development. Improving its quality and utilization remains a key challenge. This study investigated the effects of solar withering and shaking on summer green tea aroma. Sensory evaluations revealed that spreading-shaking (SR) and spreading-solar withering-shaking (SRS) significantly improved aroma, imparting floral notes. Utilizing electronic nose (E-nose), headspace solid-phase microextraction-gas chromatography–mass spectrometry (HS-SPME-GC-MS) and headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS), 61 volatile compounds were identified by HS-SPME-GC–MS and 80 by HS-GC-IMS. 9 key aroma compounds (such as geraniol and trans-β-ionone) with rOAV ≥1 and VIP ≥ 1 were selected. PLS-DA confirmed significant aroma differences among processing methods. The findings highlight the potential of solar withering and shaking in enhancing summer green tea aroma, providing a basis for optimized processing and sustainable tea production.